Informing decisions on ecosystem-based approaches for the adaptation of people in the Asia and Pacific region - Hills, T.; Pramova, E. (Center for International Forestry Research, 2011)
This brief summarises the results of a recent analysis of the awareness and information needs related to ecosystem-based approaches to adaptation in the Asia and Pacific region. These results will inform the design of a decision-support tool for development, adaptation and disaster-risk reduction stakeholders